Pengaruh Film Jumbo Terhadap Pemahaman Konsep Masalah Sosial Pada Anak Usia 5-6 Tahun Di TK Kartika II-3 Kota Palembang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of the animated film Jumbo on the understanding of social problem concepts among children aged 5-6 years at TK Kartika II-3 Palembang. The research used a quantitative one-group pretest-posttest design involving 15 children. Data were collected through structured observation sheets assessing three indicators: the ability to recognize problematic situations, identify causes and consequences, and provide simple solutions. The results showed a clear improvement after the intervention. The average pretest score was 12.53 and increased to 20.73 in the posttest, with a gain of 8.20 points. The Shapiro-Wilk test confirmed that both pretest (Sig. 0.071) and posttest (Sig. 0.239) were normally distributed. Hypothesis testing using the paired sample t-test showed a significance value of <0.001 with t = -13.575, indicating a highly significant difference between pretest and posttest scores. The research instrument also demonstrated high reliability with a Cronbach’s Alpha of 0.951. These findings confirm that the Jumbo film effectively enhances children’s understanding of social problems by presenting concrete visual situations that help them identify conflicts, understand cause-and-effect relationships, and express appropriate responses. The study concludes that the Jumbo film is a suitable audio-visual medium to support social learning and character development in early childhood education.